A Death Rate in Patients Ngudi Waluyo Blitar District Hospital - Jayanti, Krisnita Dwi; Hidayat, Andra Dwitama; Wahyuni, Titin; Prodyanatasari, Arshy; Bisono, Eva Firdayanti; Maharani, Eva Ratih (Universitas Muhammadiyah Sidoarjo, 2024)
Record by integration (RME) management efficiency has improved the health care database at the hospital, including mortality data. Mortalitas data an indicator of health service that evaluates the quality of critical care in a hospital, that is essential for decision making strategic and policy evaluation. The research aimed to identify the mortality in patients at Ngudi Waluyo Blitar District Hospital in 2023. This research used the descriptive to describe method mortality in patients at hospital Ngudi Waluyo Blitar District in 2023. The result showed that the total number of patients alive and died in 2023 was 14.485, with the number of 13410 live patients and the patient dies of 1.075. The analysis shows ICCU death as a room with the highest death, especially in time; it is < 25 ‰ or < 2.5 ‰ per year. Factors such as age, associated territories, and some septicemia as a medical condition, chronic kidney disease, stage 5, intracerebral hemorrhage, intraventricular, keys respiratory failure, and pneumonia, unspecified as the cause of death. For that reason, we need to repair constants on information systems and electronic medical records to support better decision making in the management of health services. Evaluation deep to events of death, especially in the ICCU, and focus on management of elderly patients and patients with chronic diseases such as septicemia and chronic kidney disease, be a key to increasing the quality of services.